Niosome nanocarrier enhances the ameliorating effects of myrtenol in the lungs of rats with experimental asthma - Mohammad Amin Rajizadeh; Mohammad Hadi Nematollahi; Elham Jafari; Mohammad Abbas Bejeshk; Mehrnaz Mehrabani; Mohammad Sadegh Razeghinia; Hamid Najafipour (Elsevier, 2023)
We assessed the anti-inflammatory, anti-oxidative and anti-remodeling impacts of a synthesized myrtenol-loaded niosome in rats with allergic asthma. Forty-nine rats were divided into seven groups of control, vacant niosome (VN), Asthma, Asthma+VN, Asthma+SM (simple myrtenol), Asthma+NM (niosomal myrtenol, 8 mg/kg), and Asthma+B (budesonide, 41 μg). Ovalbumin-induced asthmatic animals were exposed to daily inhalation of drug/vehicle for one week. Histopathology and inflammatory and oxidative stress indices in the lungs were assessed. Myrtenol-loaded niosomes showed appropriate physicochemical properties. Airway smooth muscle thickness, inflammatory cell infiltration, goblet cell hyperplasia, NO, IL-17, and MDA level decreased, and IL-10 and TAC levels increased in tissue and/or BALF of treatment groups. Niosomal myrtenol showed high potency comparable to budesonide in alleviating disease parameters. In conclusion, inhalation of niosomal myrtenol ameliorated inflammation, oxidative stress and tissue remodeling in asthmatic animals more potently than simple myrtenol and could be a target for production of an anti-asthmatic medicine.